2015
DOI: 10.1590/s1679-87592015086106303
|View full text |Cite
|
Sign up to set email alerts
|

Delimitation of domains in the external Río de la Plata estuary, involving phytoplanktonic and hydrographic variables

Abstract: Autumn and spring hydrological (temperature and salinity) and biological (chlorophyll, phaeopigments and phytoplankton species) variables were analysed. Phytoplankton biomass, expressed as chlorophyll a reach a maximum of 6.1 µg L-1in autumn and 22.8 µg L-1 during spring. Maxima were found in the frontal zone and marine adjacent area. Four domains were identified through multivariate analysis: Riverine, Estuarine, Frontal and Oceanic; mainly due to salinity and depth in autumn and due to salinity and chlorophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…The strong vertical stratification observed is related to the influence of colder and diluted continental water from the RdlP on the surface, and warmer and saltier oceanic shelf waters at the bottom product of the still fall presence shelf waters advected by the BC during the austral warm season. This thermal inversion is typical of this region at de beginning of the cold austral season when halinestratification determines that the surface freshwater layer loses heat rapidly (Martínez and Ortega, 2015;Piola et al, 2018). However, this stratification may be favoured by the palaeovalley geomorphology.…”
Section: Environmental Descriptionmentioning
confidence: 92%
“…The strong vertical stratification observed is related to the influence of colder and diluted continental water from the RdlP on the surface, and warmer and saltier oceanic shelf waters at the bottom product of the still fall presence shelf waters advected by the BC during the austral warm season. This thermal inversion is typical of this region at de beginning of the cold austral season when halinestratification determines that the surface freshwater layer loses heat rapidly (Martínez and Ortega, 2015;Piola et al, 2018). However, this stratification may be favoured by the palaeovalley geomorphology.…”
Section: Environmental Descriptionmentioning
confidence: 92%
“…Surface chlorophyll-a was mostly positively correlated with the nutrient distribution, decreasing toward the deep ocean. Maximum values were measured near the coast immediately offshore from the turbidity front (10 < S A < 25 g kg −1 ), although they did not peak at station 1 in the RdlP waters, where nutrient values were maximum, due to the effect on light attenuation in muddy waters (e.g., Carreto et al, 2003;Kruk et al, 2015;Martínez and Ortega, 2015). High surface fluorescence and chlorophyll-a were also observed in the southernmost area of the Uruguayan EEZ, at stations 7 and 9 over the outer shelf and slope, over the Ewing Terrace and Rio de la Plata canyon under the influence of the MC retroflection at about 37 • S 54 • W. These stations showed the coldest surface waters and high concentration of nutrients (Figures 4D-F), and also the highest integrated fluorescence in the CTD profile (3.15 mg m −3 ) in the upper 50 m (Figure 4D), as these stations were occupied at the end of a chlorophyll bloom that took place 10-25 April according to satellite observations (Supplementary Video 1).…”
Section: In Situ Observations In the Uruguayan Economic Exclusive Zon...mentioning
confidence: 99%
“…In [28], phytoplankton Chl a usually displays a concentration peak by the end of summer and the beginning of autumn, showing a unimodal trend in the seasonal pattern. There are few studies of the RdlP regarding the seasonal patterns in total chlorophyll concentration; nevertheless, recent studies have demonstrated that salinity, depth, and light availability, which attain maximum values in spring, are the main variables controlling the biomass and composition of the phytoplankton community in the RdlP [43]. …”
Section: Oceanographic Conditionsmentioning
confidence: 99%